Teachers' teaming handbook : a middle level planning guide - Arnold, John Floyd; Stevenson, Chris (Fort Worth, Tex. : Harcourt Brace College, 1998)
Background and rationale. Considerations in planning. The vital role of the principal. Developing a team vision. Governance. Organization and procedures...
Keywords: Education; Teaching; Teaching teams -- United States -- Handbooks, manuals, etc; Interdisciplinary approach in education -- United States -- Handbooks, manuals, etc; Middle schools -- United States -- Planning -- Handbooks, manuals, etc